Bio-layer Interferometry for Measuring Kinetics of Protein-protein Interactions and Allosteric Ligand Effects - Shah, Naman B. (MyJove Corporation, 2014)
We describe the use of Bio-layer Interferometry to study inhibitory interactions of subunit ε with the catalytic complex of Escherichia coli ATP synthase. Bacterial F-type ATP synthaseis the target of a new, FDA-approved antibiotic to combat drug-resistant tuberculosis. Understanding bacteria-specific auto-inhibition of ATP synthase by the C-terminal domain of subunit ε could provide a new means to target the enzyme for discovery of antibacterial drugs. The C-terminal domain of ε undergoes a dramatic conformational change when the enzyme transitions between the active and inactive states, and catalytic-site ligands can influence which of ε's conformations is predominant. The assay measures kinetics of ε's binding/dissociation with the catalytic complex, and indirectly measures the shift of enzyme-bound ε to and from the apparently nondissociable inhibitory conformation. The Bio-layer Interferometry signal is not overly sensitive to solution composition, so it can also be used to monitor allosteric effects of catalytic-site ligands on ε's conformational changes.